2012
DOI: 10.15580/gjbs.2012.1.07301217
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and chemical quality assessment of some commercially packed fruit juices sold in Nigeria

Abstract: The microbiological and chemical qualities of some commercially packed fruit juices sold in Nigeria were assessed. A total of 30 fruit juice samples were collected including Orange, Lemon, Pineapple, Punch and Guava juice. Samples were screened for total aerobic mesophilic bacterial counts which ranged from 1.4x10 4 to 2.6x10 5 cfu/ml. The fungal count ranges from 1.4x10 3 to 1.7x10 5 cfu/ml, while the coliform counts ranges from 1.1x10 4 to 6.0x10 4 cfu/ml. The isolated microbes include S. aureus, B. subtilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
(4 reference statements)
5
26
1
Order By: Relevance
“…This may indicate that the fruits used in the preparation of the juices in this study were at the state of fully maturity and ripening. The acidity values reported in this study were in agreement with those reported elsewhere (Wissanee & Renu, 2007;Oranusi et al, 2012;Rizzon & Miele, 2012;Ndife et al, 2013). However, the variations may be due to the type of fruits, their ripening stage and the season of the year, inappropriate storage of fruit and over dilution of fruit juices.…”
Section: Discussionsupporting
confidence: 92%
“…This may indicate that the fruits used in the preparation of the juices in this study were at the state of fully maturity and ripening. The acidity values reported in this study were in agreement with those reported elsewhere (Wissanee & Renu, 2007;Oranusi et al, 2012;Rizzon & Miele, 2012;Ndife et al, 2013). However, the variations may be due to the type of fruits, their ripening stage and the season of the year, inappropriate storage of fruit and over dilution of fruit juices.…”
Section: Discussionsupporting
confidence: 92%
“…Oranusi et al . [ 10 ] stated that the acceptable microbial count in fruit juices suitable for human consumption ranged from log 4 cfu/ml to log 5 cfu/ml. The microbial load on guava recorded in this study exceeded the acceptable limit.…”
Section: Discussionmentioning
confidence: 99%
“…Wine can be fermented with yeast that occurs naturally in fruits and even damaged fruits. Details on the history of wine making using fruits, fermentation process, must preparation; the effect of yeast in wine production, aging, clarification, packaging/bottling, quality assessment and evaluation of wines of different fruits can be found in [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Related analysis can be explored, see [14] , [15] , [16] , [17] , [18] for details.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%